A Cloud adoption decision support model using Influence Diagrams - Christoforou, Andreas; Andreou, Andreas S. (My University, 2013)
Cloud Computing has become nowadays a significant field of Information and Communication Technology (ICT), and this has led many organizations moving their computing operations to the Cloud. Decision makers are facing strong challenges when assessing the feasibility of the adoption of Cloud Computing for their organizations. The decision to adopt Cloud services falls within the category of complex and difficult to model real-world problems. In this paper we propose an approach based on Influence Diagrams modeling, aiming to support the Cloud adoption decision process. The developed ID model combines a number of factors which were identified through litterature review and input received from field experts. The proposed approach is validated against four experimental cases, two realistic and two real-world, and its performance proved to be highly capable of estimating and predicting correctly the right decision.
Keywords: Cloud adoption; Decision support; Influence Diagrams